Investigative techniques with regard to mafia (Rivista di Studi e Ricerche sulla criminalità organizzata, 2015)
It is republished here the text of the relation that Giovanni Falcone and Giuliano Turone, the first a palermitan judge, the other a Milanese one, both active against mafia criminality, held in a conference in Castel Gandolfo on June 1982, between Pio La Torre and Carlo Alberto dalla Chiesa’s murders. It is a historical relation, which has oriented several generation of scholars, especially for his demarcation of the three level of mafia crimes.